Molecular autopsy in a cohort of infants died suddenly at rest. (November 2018) - Campuzano, Oscar; Beltramo, Pilar; Fernandez, Anna; Iglesias, Anna; García, Laura; Allegue, Catarina; Sarquella-Brugada, Georgia; Coll, Monica; Perez-Serra, Alexandra; Mademont-Soler, Irene; Mates, Jesus; del Olmo, Bernat; et al.
Highlights: Forensic guidelines propose molecular autopsy if no conclusive cause of death. Genetic analysis may help to unravel the cause of death in infants died suddenly. A 20% of sudden infant death cases carried a potentially pathogenic variant. Careful genetic interpretation should be done before clinical translation. Abstract: Sudden infant death syndrome is the leading cause of death during the first year of life. A large part of cases remains without a conclusive cause of death after complete autopsy. In these situations, cardiac arrhythmia of genetic origin is suspected as the most plausible cause of death. Our aim was to ascertain whether genetic variants associated with sudden cardiac death might be the cause of death in a cohort of infants died suddenly. We analyzed 108 genes associated with sudden cardiac death in 44 post-mortem samples of infants less than 1 year old of age who died at rest. Definite cause of death was not conclusive in any case after a complete autopsy. Genetic analysis identified at least one rare variant in 90.90% of samples. A total of 121 rare genetic variants were identified. Of them, 33.05% were novel and 39.66% were located in genes encoding ion channels or associated proteins. A comprehensive genetic analysis in infants who died suddenly enables the unraveling of potentially causative cardiac variants in 2045% of cases. Molecular autopsy should be included in forensic protocols when no conclusive cause of death is identified. Large part genetic variants remain of uncertain significance, reinforcing the crucial role of genetic interpretation before clinical translation but also in early identification of relatives at risk.